A descriptive study of Cambodian refugee infant feeding practices in the United States - Labbok Miriam; Melvin Cathy; Straub Becky (BMC, 2008)
Abstract Background The purpose of this exploratory study was to examine Cambodian refugee mothers' infant feeding beliefs, practices, and decision making regarding infant feeding in the U.S. and to explore if a culturally-specific breastfeeding program is appropriate for this community. Methods A self-administered questionnaire and a 30 minute in-person interview were used to collect information from nine women. The audio-taped interviews were transcribed, answers compiled, and themes from each question identified. Results All participants practiced either traditional Cambodian diet (pregnancy and postpartum diet including, tnam sraa, herbs mixed with either wine or tea), traditional Cambodian rituals (like spung, amodified sauna) or both, despite having lived in the U.S. for many years. All nine women initiated breastfeeding, however eight women introduced infant formula while in hospital. Perceived low milk supply and returning to work were the main reasons cited for partial breastfeeding and early cessation of breastfeeding. Conclusion While causes of initiation of other foods are similar to those found in the U.S. as a whole, a culturally-specific Cambodian breastfeeding support program may help overcome some breastfeeding problems reported by Cambodian refugee mothers who have immigrated to the United States.